3D Stratum Interpolation Algorithm of Metro Tunnel Based on BIM and Data Fusion. (28th March 2022) - Jiang, Haidong; Yin, Jian; Chen, Yonggui; Zhang, Guofa; Peng, Xiaoyong
Abstract : The three-dimensional stratum space interpolation algorithm plays a vital role in promoting the safety, management, and decision-making of subway tunnels and is a current research hotspot. The purpose of full text is to study the 3D stratum space interpolation algorithm of subway tunnels and to study the 3D stratum space interpolation algorithm based on building information modeling (BIM) and data fusion technology. This article first uses computer three-dimensional visualization technology to simulate the surface of the ground-fall tunnel based on known data. It is to do the interpolation processing on the two-dimensional space of the subway tunnel to create an accurate surface model of the subway tunnel. It then uses the block model method to divide the internal data of the tunnel according to actual needs. In order to create a model of the internal data of the tunnel, three-dimensional spatial interpolation is performed. After the three-dimensional interpolation is completed, it is convenient to quickly estimate the taste and reserves according to the interpolation results. The experiments in the text show that the average error value of the algorithm in this paper is 38.98 and the performance is improved by 23.4%. The algorithm in the text has obvious advantages in interpolation effect, and the interpolation efficiency is faster. A bird's eye view of the current study is shown in Figure 1.